Rethinking professional autonomy: Autonomy to develop and to publish news in Mexico and Colombia (2017)
Professional autonomy has usually been defined in terms of journalists' perceptions of their control over their work vis-à-vis organizational supervisors. Using surveys of journalists in Colombia and Mexico, we identify two dimensions of perceived autonomy: first, control over story development tasks (the traditional understanding of autonomy in empirical studies); second, the ability to actually publish news on a range of subjects associated with different levels of material or cultural power. We then identify predictors of both dimensions of autonomy. Physical threats, overlapping forms of inequality, and clientelism characterize pressures on autonomy in these two democracies. Journalists can carve out more space for autonomy by gaining professional experience or by creating new organizational arrangements and supporting analytical, change-oriented norms. By examining professional autonomy empirically in a broad range of contexts, we demonstrate that autonomy is more complex, situational, and historically contingent than previously believed. © The Author(s) 2016.